1981
DOI: 10.1007/bf01295974
|View full text |Cite
|
Sign up to set email alerts
|

Acute ethanol administration increases biliary concentrations of total and unconjugated bilirubin in rabbits

Abstract: Epidemiological investigations have revealed that alcoholic cirrhosis is associated with a high frequency of pigment gallstones, but only scanty information is available on the effects of ethanol on biliary secretion of bilirubin. We have injected intravenously 1.0 and 1.5 g/kg body wt of ethanol into six cholecystectomized rabbits and a common bile duct fistula. Experiments were performed ten days after surgery and a stream-splitting apparatus was interposed in the circuit in order to withdraw continuously bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…The values obtained were similar to those previously reported by Klaassen (1974) and Esteller, Lopez and Murillo (1977) for urethane-anaesthetized animals and by Shaw and Heath (1974) and Esteller, Jimenez and Lopez (1981) for un anaesthetized animals, although they were lower than those reported by other workers for rabbits anaesthetized with pentobarbital (Erlinger et al, 1970) or for unanaesthetized animals (DiPadova et al, 1981). The data for bile acid output did not explain the differences in bile flow under the anaesthetics and point to the notion that such differences would not be related to bile-acidCollado, Pow-Andrada, Gonzalez, Jimenez & Esteller dependent secretion.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The values obtained were similar to those previously reported by Klaassen (1974) and Esteller, Lopez and Murillo (1977) for urethane-anaesthetized animals and by Shaw and Heath (1974) and Esteller, Jimenez and Lopez (1981) for un anaesthetized animals, although they were lower than those reported by other workers for rabbits anaesthetized with pentobarbital (Erlinger et al, 1970) or for unanaesthetized animals (DiPadova et al, 1981). The data for bile acid output did not explain the differences in bile flow under the anaesthetics and point to the notion that such differences would not be related to bile-acidCollado, Pow-Andrada, Gonzalez, Jimenez & Esteller dependent secretion.…”
Section: Discussionsupporting
confidence: 78%
“…In the present work two such substances widely used in the field of experimental physiology, sodium pentobarbital and ethyl urethane, were examined in an attempt to determine to what extent bile secretion and composition as well as the chemical composition of blood varies in rabbits with excluded gallbladder. In this animal species, owing to the difficulties in maintaining a chronic biliary fistula (Shaw & Heath, 1974;DiPadova et al, 1981;Esteller, Jimenez & Lopez, 1981;Jimenez, Esteller & Lopez, 1982), most studies have been carried out on animals anaesthetized with one of these agents (Klaassen, 1974;Rutishauser & Stone, 1975;Shaw & Heath, 1975;Bruss, Cornelius & Himes, 1983;Gonzalez et al, 1983;Esteller et al, 1984;Zahavi, Shaffer & Gall, 1985).…”
mentioning
confidence: 99%
“…In addition, they are in agreement with the data obtained by Di Filippo and Blumenthal [5], who described the ability of alcohol to favor pigment stone formation in hamsters in the absence of liver pathological changes. They also extend to humans previous findings that rabbits, given acute ethanol infusions, excrete increased amounts of biliary unconjugated bilirubin [6], The mechanism by which alcohol exerts this effect on biliary bilirubin is open to con jecture. According to the results of the present investigation the phenomenon is not related to changes in the activity of biliary P-glucuronidase or in the composition of bile lipids.…”
Section: Discussionsupporting
confidence: 52%
“…23]. The role of alcohol in this relationship is still unknown, but re cently we have shown that acute ethanol in fusions can induce a marked increase in the biliary level of unconjugated bilirubin in the rabbit [6].…”
mentioning
confidence: 99%
“…bilirubin loading ; bilirubin conjugation ; bilirubin excretion Though a bilirubin-loaded state is often found in patients with hemolysis, jaundice or other disorders, changes of bilirubin metabolism after bilirubin loading still remain to be defined. Previous studies on bilirubin loading in rats or other species have demonstrated the changes of bile bilirubin composition (Arias et al 1961;Gartner et al 1971;Fevery et al 1972;Noir 1976;Padova et al 1981;Trotman et al 1981;Muraga et al 1984;Munoz et al 1987;Sieg and Seitz 1987), but the influence of the loading dose or the time elapsed after loading and clearance of injected bilirubin has not been investigated in detail. This study was undertaken to investigate bilirubin clearance, conjugation and excretion after intravenous bilirubin injection in dogs with reference to the changes of bile bilirubin composition associated with the loading dose and the time elapsed after a single injection of bilirubin.…”
mentioning
confidence: 99%